Causes of Students’ Error in Writing Recount Text at 9th Grade SMPN 5 Kec. Kapur IX - Indriany, Sonya; Dewi, Merry Prima (Lembaga Yasin AlSys, 2023)
This study aims to find out the types of errors and the causes of students’ error in writing recount texts. The researchers found some student errors in the recount text at 9th grade SMP N 5 Kec.Kapur IX related to errors’ made by students. The first is that some students find it difficult to deliver idea in writing recount text. The second some students lack vocabulary so that students have difficulty in writing recount text. The last some students grammar have difficulties writing recount text. This type of research is descriptive qualitative. The instruments of this research are documentation and interview. The informant of this research is all students of class IX SMP N 5 Kec.Kapur IX which consists of 2 classes. The sample from this study was 31 students who were taken through purposive sampling. This research was conducted in February 2022. To find the type of error in writing the recount text, the researcher checked the students’ recount text answer sheets, while the researcher interviewed the students and recorded it through the researchers phone. The results of this study indicate that there is one error in writing recount text that is the use of the simple past tense. While the cause of student error based on the results of interview are carelessness, first language interference and translation. In conclusion, this study was conducted to find out the types of errors and the causes of students’ errors in writing recount texts at 9th grade SMP N 5 Kec.Kapur IX.